Development and validation of the sitting balance assessment for spinal cord injury (SitBASCI) - Guizzardi, Alessia; Artuso, Piero; Bianconi, Tatiana; Bandini, Barbara; Grotto, Enrico; Guazzini, Andrea; Sampogna, Gianluca; Caoduro, Francesca; Spinelli, Michele; Bertagnoni, Giannettore (Spinal cord, 2022)
Study design Multicentric psychometric study. Objectives The aim of this study is to introduce the development of the Sitting Balance Assessment for Spinal Cord Injury (SitBASCI) and assess its inter-rater reliability and internal consistency. Setting The study was developed among the three Spinal Units of San Bortolo Hospital in Vicenza, Niguarda Hospital in Milan and AOU Careggi in Florence. Methods SitBASCI is a 13-item scale developed to evaluate trunk control in individuals with SCI. Subjects were filmed while performing the 13 items of the scale. The videotapes were submitted to 25 examiners who evaluated patients’ performances with the scale. The power of the study was estimated. The interclass correlational coefficient (ICC) was used to assess the inter–rater reliability of the examiner’s evaluations regarding each item and the total. Cronbach’s alpha was used to assess internal consistency of the scale and internal consistency of the scale on the eliminated item. Results The study showed to have a significant power. The inter-rater reliability for the total score was p tot = 0.997 (item’s values were p = 0.876–0.998). The internal consistency of the scale was alpha = 0.925, while the internal consistency of the scale on the eliminated item was alpha = 0.912–0.930. Conclusion SitBASCI had a high inter-rater reliability and internal consistency. Items had also good inter-rater reliability and item-total correlation. Therefore, SitBASCI could be proposed as a good and reliable instrument for Italian clinicians to evaluate sitting balance and trunk control in patient with SCI despite of aetiology and level of injury.